A family's guide to Tourette syndrome - Walkup, John T.; Mink, Jonathan W.; McNaught, Kevin St. P. (Bloomington, IN : IUniverse, 2012)
Medical and scientific information about Tourette syndrome for patients, families, care providers, academic institutions, and medical centers.
The diagnosis of Tourette syndrome / James F. Leckman, Michael H. Bloch, and Robert A. King -- Psychiatric conditions associated with Tourette syndrome / Barbara J. Coffey and Amanda Zwilling -- Problems with anger, aggression, and impulse control in Tourette syndrome / Cathy L. Budman and Joanna Witkin -- How common is Tourette syndrome in children? / Lawrence Scahill -- The causes of TS and changes that occur in the brain / Jonathan W. Mink -- Inheritance, genes, and TS / Jeremiah M. Scharf and Carol A. Mathews -- Pediatric autoimmune neurophychiatric disorders associated with streptococcal infection (PANDAS) and Tourette syndrome / Tanya Murphy -- Drug treatments for Tourette syndrome and co-morbid disorders / Donald L. Gilbert -- Tourette syndrome, pregnancy and breastfeeding / Emilie R. Muelly and Cheston M. Berlin Jr. -- Behavior therapy / Matthew R. Capriotti, Flint M. Espil, and Douglas W. Woods -- Deep brain stimulation for Tourette syndrome / Michael S. Okun, Herbert Ward, Irene Malaty, Nikki Ricciuti, Candy Hill, and Kelly D. Foote -- Complementary and alternative therapies / Katie Compoliti -- The Psychosocial aspects of Tourette syndrome : a family guide and perspective / Mary May Robertson -- Living with Tourette syndrome / Samuel H. Zinner and Christine Erdie-Lalena -- Parenting a child with Tourette syndrome / Elaine Fantle Shimberg -- History and research into Tourette syndrome / Kevin St. P. McNaught -- Frequently asked questions about Tourette syndrome.
Includes bibliographical references.
Keywords: Tourette syndrome